Penelusuran Determinan Peningkatan Kinerja Karyawan: (Tracking of Determinants of Employee Performance Improvement) - Aprih Santoso; Nurul Afifah (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2020)
This study aims to determine the effect of Leadership, Work Motivation, Work Discipline and Work Environment on the Performance of Employees of PT. Wingtech Technology Indonesia. In this study were the production employees of PT. Wingtech Technology Indonesia. The data used in this study are primary data by distributing questionnaires to production employees of PT. Wingtech Technology Indonesia. The sample in this study were 82 respondents, the sampling technique using purposive sampling. Data collection methods in this study were questionnaire and data analysis. Data is processed using SPSS 24, including Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing using T Test, F Test and R2 Test.The results of this study indicate that Leadership, Work Motivation, Work Discipline and the Work Environment have a positive and significant impact on Employee Performance at PT. Wingtech Technology Indonesia. The coefficient of determination (Adjusted R2) is 0.740, which means that Leadership, Work Motivation, Work Discipline and the Work Environment have a 74% effect on Employee Performance and the remaining 26% is explained by other factors beyond the variables studied. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Kepemimpinan, Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Wingtech Technology Indonesia. Dalam penelitian ini adalah karyawan produksi PT. Wingtech Technology Indonesia. Data yang digunakan dalam penelitian ini adalah data primer dengan menyebar kuesioner kepada karyawan produksi PT. Wingtech Technology Indonesia. Sampel dalam penelitian ini sebanyak 82 responden, teknik pengambilan sampel menggunakan purposive sampling. Metode pengumpulan data dalam penelitian ini adalah kuesioner dan analisis data. Data diproses dengan menggunakan SPSS 24, meliputi Uji Validitas, Uji Reliabilitas, Uji Asumsi Klasik, Analisis Regresi Linier Berganda dan Pengujian Hipotesis menggunakan Uji T, Uji F dan Uji R2. Hasil penelitian ini menunjukkan Kepemimpinan, Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja berpengaruh positif dan signifikan terhadap Kinerja Karyawan di PT. Wingtech Technology Indonesia. Koefisien determinasi (Adjusted R2) diperoleh sebesar 0,740 yang berarti Kepemimpinan, Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja berpengaruh 74% terhadap Kinerja Karyawan dan sisanya 26% dijelaskan faktor-faktor lain diluar variabel yang diteliti.